Reproduction of Meloidogyne enterolobii on selected root-knot nematode resistant sweetpotato (Ipomoea batatas) cultivars - Brito, Janete A. (J Nematol, 2020)
The ability of Meloidogyne enterolobii to reproduce on selected sweetpotato (Ipomoea batatas) cultivars (Beauregard, Covington, Evangeline, Hernandez, and Orleans (LA 05-111)) was evaluated in two greenhouse experiments, each with 10 replicates. All cultivars, except Beauregard (control) and Orleans, were reported previously as moderately resistant or resistant to M. incognita, Fusarium oxysporum f. sp. batatas, and Streptomyces ipomoeae. Plants were inoculated with M. enterolobii (5,000 eggs/plant) and arranged in a completely randomized design in a greenhouse with an average daily temperature of 24.8°C. Galls and egg masses per root system (0-5 scale), eggs per egg mass, eggs per gram of fresh root (gfr), and reproduction factor (RF) were determined. Meloidogyne enterolobii infected and reproduced on all the sweetpotato cultivars. The nematode induced galls on both fibrous and storage roots, regardless of the cultivar, as well as induced necrosis and cracks on storage roots. The lesions and cracks on the storage roots were more visually pronounced on Hernandez than those on other cultivars. Cultivar Orleans sustained less root galling and egg masses than other cultivars (p ≤ 0.01), and both Orleans and Beauregard cultivars had less eggs per gfr and a lower RF than Covington (5,683 eggs/gfr; RF = 16.92), Evangeline (7,161 eggs/gfr; RF = 30.01), and Hernandez (6,979 eggs/gfr; RF = 22.6). The latter two cultivars sustained the largest amount of reproduction of M. enterolobii. The number of eggs per egg mass ranged from 462 to 503 and was similar among all cultivars. In summary, M. enterolobii reproduced well on all sweetpotato cultivars; however, differences were observed among cultivars (p ≤ 0.001). The host status as previously reported for other root-knot nematode species was not a good predictor of host status to M. enterolobii. Some sweetpotato cultivars that were reported as resistant or moderately resistant to M. incognita race 3, such as Evangeline and Hernandez, were among the best hosts to M. enterolobii. Root growth of Evangeline and Orleans, but not of the other cultivars, was negatively correlated with nematode eggs per gfr.